Adoptive immunotherapies in neuro-oncology: classification, recent advances, and translational challenges - Luzzi, Sabino; Giotta Lucifero , Alice; Brambilla, Ilaria; Magistrali, Mariasole; Mosconi, Mario; Savasta, Salvatore; Foiadelli, Thomas (Acta Biomedica Atenei Parmensis, 2020)
Background: Adoptive immunotherapies are among the pillars of ongoing biological breakthroughs in neuro-oncology, as their potential applications are tremendously wide. The present literature review comprehensively classified adoptive immunotherapies in neuro-oncology, provides an update, and overviews the main translational challenges of this approach. Methods: The PubMed/MEDLINE platform, Medical Subject Heading (MeSH) database, and ClinicalTrials.gov website were the sources. The MeSH terms “Immunotherapy, Adoptive,” “Cell- and Tissue-Based Therapy,” “Tissue Engineering,” and “Cell Engineering” were combined with “Central Nervous System,” and “Brain.” “Brain tumors” and “adoptive immunotherapy” were used for a further unrestricted search. Only articles published in the last 5 years were selected and further sorted based on the best match and relevance. The search terms “Central Nervous System Tumor,” “Malignant Brain Tumor,” “Brain Cancer,” “Brain Neoplasms,” and “Brain Tumor” were used on the ClinicalTrials.gov website. Results: A total of 79 relevant articles and 16 trials were selected. T therapies include chimeric antigen receptor T (CAR T) cell therapy and T cell receptor (TCR) transgenic therapy. Natural killer (NK) cell-based therapies are another approach; combinations are also possible. Trials in phase 1 and 2 comprised 69% and 31% of the studies, respectively, 8 of which were concluded. CAR T cell therapy targeting epidermal growth factor receptor variant III (EGFRvIII) was demonstrated to reduce the recurrence rate of glioblastoma after standard-of-care treatment. Conclusion: Adoptive immunotherapies can be classified as T, NK, and NKT cell-based. CAR T cell therapy redirected against EGFRvIII has been shown to be the most promising treatment for glioblastoma. Overcoming immune tolerance and immune escape are the main translational challenges in the near future of neuro-oncology.